Development of learning media powerpoint-iSpring integrated with prompting questions on stoichiometry topics - Sulta Hanika; Guspatni Guspatni (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
PowerPoint-iSpring is one of the technology-based media needed in learning. Giving guiding questions is expected so students can find concepts independently through exercises and questions in the media. This study aims to develop PowerPoint-iSpring learning media integrated with prompting questions on stoichiometry class X SMA. The development model used was the Plomp model, which was carried out until the stage of prototype III formation due to time and research staff limitations. Researchers self-evaluate media that has been designed to determine the completeness of the components of a media. Then an assessment was carried out by experts consisting of four chemistry lecturers at FMIPA UNP and two chemistry teachers at SMAN 10 Padang. Three students of SMAN 10 Padang carried out the individual evaluation stage (one-to-one evaluation) with different abilities. The research instruments used were validity questionnaire sheets and interview sheets. The validity questionnaire was analyzed using the Aiken V formula with a category ≥0.79 valid and if <0.79 ​​is invalid. The research results found that the average value of Aiken V PowerPoint-iSpring learning media on stoichiometry material for content validity was 0.88, and construct validity was 0.87. Technical quality validity was 0.93, with each validity being categorized as valid. The results of the one-to-one evaluation obtained from 3 students were good. The suggestion is that it would be better if these media were small so they could be installed on a device without requiring much space. The images that covered the writing explaining the material would be better if the layout was improved.